Juridical Study of Industrial Relations Dispute Resolution Mechanism Due to Unilateral Termination of Employment By PT. Bisa Group - Muhammad Rizky Syamandiri (Syntax Idea, 2082)
Arrangements related to the settlement of current relationship disputes are no longer considered to be able to accommodate and regulate various developments that occur, because the rights of individual workers / workers have not been fulfilled and protected properly in industrial relations disputes, especially such as industrial relations disputes caused by unilateral termination of employment by the company, where workers must lose and give up their jobs without obtaining the rights that should be accepted by the worker, and this is not in accordance with what is and regulated in the Manpower Law, as happened in the case of unilateral termination of employment (layoff) of an employee by the company PT. Can Group. Therefore, the formulation of the problem in this study is how legal protection for workers / laborers due to unilateral termination of employment by a company, and the method used in this study is a normative legal research method